1990
DOI: 10.3382/ps.0690640
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Purification, and the Amino Acid Sequence of a Secretory Trypsin Inhibitor from the Chicken Pancreas

Abstract: A trypsin inhibitor is secreted in the pancreatic juice of the chick. Extracts from tissue have an inhibitor that corresponds to the secreted inhibitor on the basis of chromatography on DEAE-cellulose. The secretory inhibitor was purified by anion- and cation-exchange chromatography and by preparative isoelectric focusing. The purified inhibitor has 69 amino acids and is highly homologous with the secretory inhibitor from the turkey pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In addition to the enzymes reported in that study, an elastase, three forms of chymotrypsin, and a secretory trypsin inhibitor have also been found in the chick in the present study ( Figure 1, Table 1). The trypsin inhibitor secreted by the chick pancreas (Pubols, 1990) is highly homologous with inhibitors secreted by the pancreas from mammals and the turkey (Bogard and Laskowski, 1979;Laskowski et al, 1987). An earlier report from the author's laboratory had indicated that a similar profile of enzymes was present in pancreatic juice from the chick (Dal Borgo et al, 1968a).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to the enzymes reported in that study, an elastase, three forms of chymotrypsin, and a secretory trypsin inhibitor have also been found in the chick in the present study ( Figure 1, Table 1). The trypsin inhibitor secreted by the chick pancreas (Pubols, 1990) is highly homologous with inhibitors secreted by the pancreas from mammals and the turkey (Bogard and Laskowski, 1979;Laskowski et al, 1987). An earlier report from the author's laboratory had indicated that a similar profile of enzymes was present in pancreatic juice from the chick (Dal Borgo et al, 1968a).…”
Section: Resultsmentioning
confidence: 97%
“…The mixture of trypsin and trypsin inhibitor was allowed to react for 1 min at room temperature (23 C) before assay. For standardization, the amount of inhibitor required to reduce the rate of TAME hydrolysis by 50% was used for assays (Greene et al, 1966;Pubols, 1990).…”
Section: Trypsin Inhibitor Assaymentioning
confidence: 99%
“…clTI-1 reveals close homology to the chicken Kazal-type serine proteinase inhibitor precursor [35], which is similar to the proteinase inhibitor isolated from seminal plasma of turkey [11]. High homology to the other members of Kazal-type family, especially to acrosin-trypsin inhibitors [36,37], pancreatic secretory trypsin inhibitors [27,28,31,32,[38][39][40], ovomucoids, and chicken ovoinhibitor, was revealed as well (Fig. 8).…”
Section: Determination Of the Primary Structure Of Clti-1mentioning
confidence: 95%
“…clTI-1 consists of a single polypeptide chain of 55 (54) amino acids. The amino acid composition of purified inhibitor is similar to that of Kazal-type inhibitors of other species [27][28][29][30][31][32][33][34]. It contains six Cys residues, suggesting that three disulfide bonds are present in the three-dimensional structure.…”
Section: Determination Of the Primary Structure Of Clti-1mentioning
confidence: 97%
See 1 more Smart Citation